Lifetime Learning and an inclusive psychopedagogy for adults: Positive Effects of Academic Quality Management in the Psychopedagogy Master's Degree at UNED (Revista Electrónica Calidad en la Educación Superior, 2025)
This article explores the influence of academic quality management processes on the Professional Master Program in Psychopedagogy curricular updating. Additional, it delves into the incorporation of new perspectives, such as Lifelong Learning and attention to diversity in adult education. Using a qualitative approach and a Situational Analysis design, the study identifies strategies that promote equity, accessibility, and educational innovation within the master program. The findings highlight the importance of integrating andragogy and technology to foster flexible and adaptive training in diverse contexts. The study concludes that strengthening continuing education is essential for professional development in a rapidly changing society.
Keywords: lifelong learning; psychopedagogy; andragogy; academic quality; accreditation; continuous improvement